Facile Fabrication of High‐Density Sub‐1‐nm Gaps from Au Nanoparticle Monolayers as Reproducible SERS Substrates. (6th October 2016) - Si, Shaorong; Liang, Wenkai; Sun, Yinghui; Huang, Jing; Ma, Weiliang; Liang, Zhiqiang; Bao, Qiaoliang; Jiang, Lin
Abstract : The fabrication of ultrasmall nanogaps (sub‐1 nm) with high density is of significant interest and importance in physics, chemistry, life science, materials science, surface science, nanotechnology, and environmental engineering. However, it remains a challenge to generate uncovered and clean sub‐1‐nm gaps with high density and uniform reproducibility. Here, a facile and low‐cost approach is demonstrated for the fabrication of high‐density sub‐1‐nm gaps from Au nanoparticle monolayers as reproducible surface‐enhanced Raman scattering (SERS) substrates. Au nanoparticles with larger diameters possess lower surface charge, thus the obtained large‐area nanoparticle monolayer generates a high‐density of sub‐1‐nm gaps. In addition, a remarkable SERS performance with a 10 11 magnitude for the Raman enhancement is achieved for 120 nm Au nanoparticle monolayers due to the dramatic increase in the electromagnetic field enhancement when the obtained gap is smaller than 0.5 nm. The Au nanoparticle monolayer is also transferred onto a stretchable PDMS substrate and the structural stability and reproducibility of the high‐density sub‐1‐nm gaps in Au monolayer films are illustrated. The resultant Au nanoparticle monolayer substrates with an increasing particle diameter exhibit tunable plasmonic properties, which control the plasmon‐enhanced photocatalytic efficiency for the dimerization of p ‐aminothiophenol. The findings reported here offer a new opportunity for expanding the SERS application. Abstract : A facile and low‐cost approach is demonstrated for the fabrication of high‐density sub‐1‐nm gaps from Au nanoparticle monolayers as reproducible surface‐enhanced Raman scattering (SERS) substrates. Remarkable SERS performance with a 10 11 magnitude Raman enhacement is achieved for 120 nm Au nanoparticle monolayers due to the dramatic increase in the electromagnetic field enhancement when the obtained gap is smaller than 0.5 nm.